Prevalence of Early Childhood Caries in Southern Italy: An Epidemiological Study - Grazia Fichera; Simona Santonocito; Vincenzo Ronsivalle; Alessandro Polizzi; Salvatore Torrisi; Ludovica Deodato; Giuseppe Palazzo; Gaetano Isola (Hindawi Limited, 2021)
The purpose of this study was to assess the prevalence of Early Childhood Caries (ECC) and oral habits among preschool children from a southern Italian cohort. The survey population consisted of 300 subjects randomly selected among children attending two kindergartens in Catania, Italy. The prevalence of ECC and oral habits were clinically evaluated. During the clinical evaluation, the oral hygiene of children was also assessed. Parents were also interviewed using a brief and simple online questionnaire aimed at investigating eating and oral hygiene habits. The selected sample age ranged between 3 and 5 years. The prevalence of ECC was 9.34%, and the most affected teeth were primary molars. Moreover, the prevalence of oral habits was 44.66%. Only two-thirds of the sample brush their teeth at least once per day. The prevalence of ECC among Sicilian children (9.33%) seems suitable with the rest of the country. The results of the present study evidenced that oral habits showed a high prevalence among preschool children. The level of oral hygiene among preschool children is still not sufficient.